2011
DOI: 10.1007/s12160-011-9299-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relative Effectiveness of Three HIV Testing Strategies Targeting African American Men Who Have Sex with Men (MSM) in New York City

Abstract: Findings suggest differential effectiveness of testing strategies. Given differences in the individuals accessing testing across strategies, a multi-strategic testing approach may be needed to most fully identify undiagnosed HIV-positive African American MSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 26 publications
(43 reference statements)
4
35
0
3
Order By: Relevance
“…These findings are similar to those reported by Kimbrough et al (2009), whose research showed that social networks were very effective in recruiting persons in high-risk networks. Published studies have reported similar findings that support using social networks to reach persons at high risk for HIV and other STDs (Halkitis et al, 2011;Rothenberg et al, 2000). In this study, each site was required to implement all three strategies.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These findings are similar to those reported by Kimbrough et al (2009), whose research showed that social networks were very effective in recruiting persons in high-risk networks. Published studies have reported similar findings that support using social networks to reach persons at high risk for HIV and other STDs (Halkitis et al, 2011;Rothenberg et al, 2000). In this study, each site was required to implement all three strategies.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, the social network strategy is an especially important public health tool because the same social networks through which HIV infection occurs can be accessed for early detection and prevention of new infections (Adimora & Schoenbach, 2005;CDC, 2005;Kimbrough et al, 2009). A recent evaluation of multiple recruitment strategies to identify HIV-positive African American men who have sex with men (MSM) for HIV testing found social networks to be most effective, followed by partner services and alternate venues (Halkitis et al, 2011). Although the social network strategy may require more effort, it may reach certain high-risk women who would not be reached through targeted outreach and alternate venues; reaching them before they become infected may afford them an opportunity to reduce their risk.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Despite engaging in high-risk HIV related behaviors including substance use, concurrency, improper or non-condom usage, many indiviudals have perceived their risk for contracting HIV as low. This low perceived risk has been associated with African Americans not seeking HIV testing despite their actual risk profile.…”
Section: Factors Impacting Hiv Testingmentioning
confidence: 99%
“…45 Many of the implementation challenges highlighted by these demonstration projects and other published studies examining various HIV testing strategies readily lend themselves to OR. 46,47 At a minimum, OR must identify optimal strategies for reaching high-risk persons to increase early detection, receipt of test results, and linkage to medical care. Effective strategies must be developed and disseminated to ensure that persons who receive preliminary test results also receive confirmatory results, to enhance partner services programs to identify new HIV-positive persons, and to strengthen the implementation of self-testing.…”
Section: Hiv Testing In Clinical and Nonclinical Settingsmentioning
confidence: 99%